Peningkatan Hasil Belajar Matematika dengan Metode Daring pada Pembelajaran Jarak Jauh - Irmayanti Irmayanti (Institut Agama Islam Negeri (IAIN) Samarinda, 2022)
The corona pandemic since the end of 2019 has caused learning activities to be carried out distantly or PJJ (Distance Learning). Teaching Mathematics through PJJ with the online method has generated various obstacles, including student discipline that is difficult to control and difficulties in independent learning due to material that requires high abstraction skill. This has made the learning outcomes of most students do not reach the Minimum Mastery Criteria (KKM). The purpose of this research is to improve the students’ mathematics learning outcomes on Number Patterns material during PJJ. In order to achieve learning objectives, improvements are made to the learning process with the MERDEKA technique, which is an acronym for Motivation, Education, Repetition, Discussion, Evaluation, Competition and Action. Furthermore, this study is aimed at finding out the student's response to online learning by the researcher. This Classroom Action Research consists of 2 cycles with 181 Grade VIII students of MTs Negeri Samarinda as research subjects in Academic Year 2020/2021. From this study, it can be concluded that the MERDEKA interaction technique in teaching and learning mathematics conducted online could improve student learning outcomes on Number Patterns material. The students’ response to the teacher’s learning is also favorable. It is proven that the presence of students is more than 85% on average, more than 85% of students admit that the teacher's teaching methods are fun and more than 75% convey that they understand the teacher's explanations in the teaching and learning process.